1997
DOI: 10.1046/j.1570-7458.1997.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Bistability’ experiments and the photoperiodic clock in the spider mite Tetranychus urticae

Abstract: Link to publication Citation for published version (APA):Vaz Nunes, M., & Veerman, A. (1997). "Bistability" experiments and the photoperiodic clock in the spider mite tetranychus urticae. Entomologia Experimentalis et Applicata, 84,[195][196][197]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…In this way, it was shown that the spider mite's clock resembles an hourglass, and the observed positive results of NandaHamner and Bünsow experiments were assumed to be due to the resonance effect of the circadian system on the counter (Model 3). The negative results of bistability experiments agreed with this model (Vaz Nunes and Veerman, 1997).…”
Section: Experimental Tests Of Clock Models and Their Use In Guiding supporting
confidence: 81%
“…In this way, it was shown that the spider mite's clock resembles an hourglass, and the observed positive results of NandaHamner and Bünsow experiments were assumed to be due to the resonance effect of the circadian system on the counter (Model 3). The negative results of bistability experiments agreed with this model (Vaz Nunes and Veerman, 1997).…”
Section: Experimental Tests Of Clock Models and Their Use In Guiding supporting
confidence: 81%
“…T‐experiments and symmetrical skeleton photoperiods in the ‘zone of bistability’ (see above) have failed to provide evidence, in T. urticae , for a circadian involvement in photoperiodism (Vaz Nunes & Veerman, 1997). However, this may have been due to the relatively weak (short) 1‐h pulses of light used in these experiments.…”
Section: Damping Circadian Oscillator(s) As Photoperiodic Clocksmentioning
confidence: 99%